Peran Dinas Pariwisata dalam Pengelolaan Wisata Minat Khusus di Kabupaten Ponorogo - Rahmawati, Nurul; Hilman, Yusuf Adam; Triono, Bambang (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
Special interest tourism is a tour aimed at tourists who have a specific purpose or interest and motivation in traveling. In Ponorogo Regency itself, which is classified as special interest tourism on the Tourism Office website there are several tours such as Gunung Gajah Tour, Tanah Goyang Tour, Bedes Mountain Tour, and Pumpak Pare tour. But the existence of the tour all had only briefly gone viral but after a few months no longer heard the news. This study wants to find out how the role of the Department of Tourism in the Management of Special Interest Tourism in Ponorogo Regency. The purpose of this study is to find out the role of the Ponorogo Tourism Office and to know what obstacles are faced by the Ponorogo Tourism Office in the Management of Special Interest Tourism in Ponorogo Regency. The research method used is qualitative. The process of collecting data by interviewing the heads of community information groups in the district of Ponorogo. Data can be obtained from interview scripts, field notes or memos, and official documents. This analysis uses four indicators, namely Planning, Organizing, Movement and Supervision. The Tourism Office itself is seen as lacking in providing guidance and assistance in managing the specially meant tourism itself. many villages or tourism managers do not receive training, coaching, and assistance that is uneven, they are as if not noticed by the Department of Tourism. It can be concluded that the role of the Ponorogo Office has not been maximized and there are many shortcomings in training, guidance, assistance, and monitoring carried out by the Pariwsata Office, not necessarily and there is an imbalance in carrying out all of its duties and responsibilities.